(untitled) (Journal of Pharmaceutical Negative Results, 2023)
An efficient one pot multicomponant approach for the synthesis of 1, 8-dioxo-octahydroxanthene derivatives. We have developed a novel method for the synthesis of series of bioactive heterocyclic compounds. Ag-CP MOFs as heterogeneous catalyst and use of Ethanol as a green solvent makes the protocol attractive from sustainability point of view. A highlight of our approach is easy separation of catalyst from the reaction medium and so on recyclability of the catalyst. This is simple method is applicable to access wide range of aromatic aldehydes for the synthesis of 1, 8-dioxo-octahydroxanthenes derivatives. The as synthesized derivatives were well characterized by 1HNMR spectroscopy. The results show that the novel Ag-CP MOFs as heterogeneous catalyst was very efficient for the traditional reactions with good to excellent yields in short time.